Fruit color and contrast in seasonal habitats - a case study from a cerrado savanna - Camargo, Maria Gabriela G. [UNESP]; Cazetta, Eliana; Schaefer, H. Martin; Morellato, L. Patrícia C. [UNESP] (Wiley, 2013)
Communication contributes to mediate the interactions between plants and the animals that disperse their genes. As yet, seasonal patterns in plant-animal communication are unknown, even though many habitats display pronounced seasonality e.g. when leaves senescence. We thus hypothesized that the contrast between fruit displays and their background vary throughout the year in a seasonal habitat. If this variation is adaptive, we predicted higher contrasts between fruits and foliage during the fruiting season in a cerrado-savanna vegetation, southeastern Brazil. Based on a six-year data base of fruit ripening and a one-year data set of fruit biomass, we used reflectance measurements and contrast analysis to show that fruits with distinct colors differed in the beginning of ripening and the peak of fruit biomass. Black, and particularly red fruits, that have a high contrast against the leaf background, were highly seasonal, peaking in the wet season. Multicolored and yellow fruits were less seasonal, not limited to one season, with a bimodal pattern for yellow ones, represented by two peaks, one in each season. We further supported the hypothesis that seasonal changes in fruit contrasts can be adaptive because fruits contrasted more strongly against their own foliage in the wet season, when most fruits are ripe. Hence, the seasonal variation in fruit colors observed in the cerrado-savanna may be, at least partly, explicable as an adaptation to ensure high conspicuousness to seed dispersers. © 2013 The Authors.
Keywords: adaptation; biomass; cerrado; color morph; data set; foliage; fruit; habitat type; ripening; savanna; seasonal variation; seasonality; seed dispersal; Brazil; Animalia